Assessment of women's knowledge about cytology as a prophylactic method in cervical cancer - Standyło, Arkadiusz; Obuchowska, Aleksandra; Wójcik, Justyna; Ozga, Alicja; Obuchowska, Karolina (Journal of Education, Health and Sport, 2020)
Introduction Cervical cancer (CC) is currently the eight most common cancer among women and the seventh leading cause of cancer-related death in women in Poland. Early, non-invasive cervical cancer may develop over the years without clinical symptoms. Also, given the fact that early forms are treatable effectively, it's important to get preventive examinations. It is especially important in the group of women at high risk of developing CC. Purpose The aim of the study was to analyse the opinions of 1,260 women on the cytology as a prophylactic method in cervical cancer. Material and methods Women's knowledge was verified with an anonymous online questionnaire. The obtained results were analysed and checked on the basis of scientific literature. Results The vast majority of respondents (89,6%) consider Pap smear test as a screening test for CC. According to 40.4% of women, the first test should take place after sexual initiation. 17.7% believed that the examination should be done after the first menstruation. 55% of the respondents answered that Pap smear test should be performed every year. 38.4% believed that the test should be performed every 3 year. 20.3% of respondents do not know when to take the first Pap smear test and 30.1% of the respondents had never performed a pap smear. Conclusions Most women know the importance of regular cytology, but unfortunately not all women relate this knowledge to themselves. Early, regular and continuous education of women on the prevention of cervical cancer is extremely important